2016
DOI: 10.1111/apt.13511
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the adverse effects of tobacco smoking on the natural history of Crohn's disease

Abstract: Summary Background Tobacco smoking is a well‐established risk factor for the development of Crohn's disease, and this may lead to a more complicated disease course. However, recent evidence suggests that many patients with Crohn's disease are unaware of this fact. Aim To perform a systematic review and meta‐analysis of the effects of smoking on disease course in Crohn's disease. Methods A search of MEDLINE, EMBASE and EMBASE classic was carried out (up to July 2015) to identify observational studies reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
94
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 85 publications
(221 reference statements)
9
94
2
1
Order By: Relevance
“…In a recent meta-analysis, To et al ( 174 ) found in 33 studies a 56% higher risk of a fl are of disease activity and a twofold risk of fl are aft er surgery along with a need for fi rst surgery (OR 1.68; 95% CI, 1.33-2.12) and the need for second surgery (OR 2.17; CI, 1.63-2.89) in smokers.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In a recent meta-analysis, To et al ( 174 ) found in 33 studies a 56% higher risk of a fl are of disease activity and a twofold risk of fl are aft er surgery along with a need for fi rst surgery (OR 1.68; 95% CI, 1.33-2.12) and the need for second surgery (OR 2.17; CI, 1.63-2.89) in smokers.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Guarantor of the article: Gilaad G. Kaplan 54% more likely to require a fi rst intestinal resection as compared with non-smokers ( 13 ). Patients who continue to smoke following the fi rst operation have an over twofold increased risk of experiencing clinical postoperative recurrence ( 14 ) and need for second intestinal resection ( 13 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Patients who continue to smoke following the fi rst operation have an over twofold increased risk of experiencing clinical postoperative recurrence ( 14 ) and need for second intestinal resection ( 13 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…DEAR SIRS, We read with great interest the systematic review with meta-analysis by To et al 1 regarding the effects of smoking on disease course in Crohn's disease (CD). The authors analyzed 33 studies comparing CD patients, smokers vs. nonsmokers, and observed that smokers had increased odds of flare of disease activity (OR, 1.56), flare after surgery (OR, 1.97), need for first surgery (OR, 1.68) and need for second surgery (OR, 2.17).…”
mentioning
confidence: 99%